Digital Diet and Relevant Minority Aspects during Home Preschool Education - Barabási, Tünde; Stark, Gabriella Mária (Central European Journal of Educational Research, 2022)
The aim of the present research is to provide an outline of the home education situation of Hungarian children enrolled in educational institutions in Romania. The research focuses on the perspective of early childhood teachers and education experts. Our objective is to identify the factors influencing the digital diet in minority preschool education and investigate whether this phenomenon, along with practices in home education, have specific distinguishing features as compared to trends in mainstream education. Approaches to digital diet and preschoolers’ use of digital tools are basic components of our interpretative framework. We set out to investigate this pedagogical phenomenon in the light of minority education, considering the educational situation in dispersed and block regions. Our descriptive study, built on a questionnaire (own design), presents the good practices in home education focusing specifically on minority aspects. Our sample consisted of 403 early childhood teachers and 14 minority education experts resulting from convenience sampling. The investigation reveals a more liberal home education style. According to experts, the national regulatory framework for home education gives rise to conflicting interpretations and specific minority provisions and recommendations are less straightforward. During home education, the proportion of the areas of development and that of learning content is distorted, and the language of instruction as a factor influencing the digital diet becomes especially prominent. Research results did not focus primarily on the minority features of home education and the digital diet but rather on regional and local distinguishing features.